Determination of Passenger Car Unit and Capacity at Grades of Two Lane Undivided Highway: A Case Study of Khurkot–Dhulikhel Section of BP Highway - Malla, Suresh; Shahi, Thusitha Chadani; Malla, Tek Bahadur (International Journal on Engineering Technology, 2024)
The majority of Nepal’s National Highway and feeder road system comprises two-lane highways with heterogeneous traffic conditions. Factors such as lane width, gradient, lateral clearance, and shoulder conditions can influence the passenger car unit (PCU) and roadway capacity. Recognizing that grade magnitude (%) is an important yet unexplored roadway factor in Nepal, and the present study primarily aims to estimate the passenger car unit on two-lane undivided hilly roads with gradients under prevailing heterogonous traffic conditions. This study aims to determine the PCU values and roadway capacity at grade under mixed nature traffic flow for a two-lane undivided highway. In this research, the necessary data were collected at five sections of BP highways using a digital video recorder, which was then analyzed to assess traffic characteristics and calculate PCU values. Using the PCU values, the road capacity was estimated using Greenshield’s model. For capacity estimation, flow and density were addressed using dynamic PCU values. This study reveals that the PCU of all categorized vehicles increases linearly with the increase in gradient while roadway capacity decreases with an increase in grade. It was observed that PCU values obtained for two-wheelers in all sections are smaller than the PCU values specified in NRS 2013, whereas for buses, trucks, and LCVs, they are higher than the PCUs given in NRS 2013. The study highlights the impact of road grade on the PCU for different vehicle categories on a highway. Additionally, the study demonstrates that the developed capacity values are realistic and consistent with the values presented in the Highway Capacity Manual (HCM) of developing countries such as Indonesia and China. These results are expected to be beneficial for practitioners and the ongoing effort to develop a highway capacity manual.